(untitled) (The Review of Diabetic Studies, 2024)
The Kingdom of Saudi Arabia has been undergoing one of the most significant health sector reforms in its modern history as part of Vision 2030 — a national strategy to diversify the economy and improve quality of life. Central to this transformation is the role of healthcare practitioners (physicians, nurses, allied health professionals, public health workers) in advancing public health outcomes and ensuring resilient health systems. This review synthesizes current evidence on the healthcare workforce in Saudi Arabia, their contributions to public health, workforce challenges (including Saudization, skill gaps, and workforce distribution), and policy strategies to strengthen capacity. It also highlights opportunities for workforce development through education, training, digital health integration, and intersectoral collaborations, concluding with recommendations for policy and future research.